Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1063/1.2821907
|View full text |Cite|
|
Sign up to set email alerts
|

Rayleigh–Taylor shock waves

Abstract: Beginning from a state of hydrostatic equilibrium, in which a heavy gas rests atop a light gas in a constant gravitational field, Rayleigh–Taylor instability at the interface will launch a shock wave into the upper fluid. We have performed a series of large-eddy simulations which suggest that the rising bubbles of light fluid act like pistons, compressing the heavy fluid ahead of the fronts and generating shocklets. These shocklets coalesce in multidimensional fashion into a strong normal shock, which increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…The Miranda code has been used extensively for simulating turbulent flows with high Reynolds numbers and multicomponent mixing 6,9,24,25 . Miranda uses a 10 th -order compact differencing scheme for spatial differentiation and a 5-stage, 4…”
Section: B the Miranda Codementioning
confidence: 99%
“…The Miranda code has been used extensively for simulating turbulent flows with high Reynolds numbers and multicomponent mixing 6,9,24,25 . Miranda uses a 10 th -order compact differencing scheme for spatial differentiation and a 5-stage, 4…”
Section: B the Miranda Codementioning
confidence: 99%
“…At larger reference pressures, the initial stratification is reduced, so that the pressure can also be interpreted as a stratification parameter [65,66]. This could lead to some analogies to the rich literature on stably stratified flows; however, within the mixing layer, finite pressure values have clear compressibility effects implications, as they can lead to the formation of shock waves [13]. In addition, the interpretation of pressure as a stratification parameter makes sense only for some particular cases of unperturbed flows (e.g.…”
Section: (C) Continuum Descriptions (I) Navier-stokes Equationsmentioning
confidence: 99%
“…Compressible NS equations solvers, on the other hand, pose their own challenges owing to the very large range of dynamically relevant spatio-temporal scales present in the compressible RTI layer. As recent results suggest [13], besides the intrinsic broad range of turbulent scales, such flow also generates shock waves that further extend the dynamically relevant range of scales. One promising approach for such problems, at least at early to intermediate times, when the turbulence is highly localized, is to use an adaptive mesh refinement technique and such approaches are discussed below.…”
Section: Numerical Solutions To the Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A somewhat analogous phenomenon has been observed in RayleighTaylor instability. 56 For Rayleigh-Taylor instability, Olson and Cook observed that the acceleration of an interface driven by a constant gravitational field generated shocklets, much in the same way a piston does, which eventually catch up to one another to form a weak shock. Presently, in "heavy-to-light" Richtmyer-Meshkov instability, we observe incipient weak shock waves generated by oscillations in the material contact.…”
Section: A Amplitude and Growth Ratementioning
confidence: 99%